Use of innovative methods in teaching subjects - Eshimova Nilufar Nurmukhammadovna (Zien Journals, 2022)
Simple lectures, which are the teacher's hourly monologues, are no longer interesting to modern students. They are easily bored and express it openly. A university or vocational school teacher must now not only engage but also captivate the audience's attention. For these goals, cutting-edge instructional technologies are being developed.
Keywords: method; style; brainstorming; discussion